Applied Surface Science - Injeti, Gurrappa (IntechOpen, 2019)
This book covers the state of the art and recent advances in the field of surface science of a variety of materials for different applications and provides an in-depth understanding of mechanisms involved in achieving the desired surface properties. The book is extremely useful to materials scientists, system design engineers, maintenance engineers, manufacturing experts and executives, industrialists, mechanical engineers, chemical engineers, aeronautical engineers, academic researchers, and undergraduate and postgraduate students.